Nano- and micro-structures in lunar zircon from Apollo 15 and 16 impactites: implications for age interpretations - Monika A. Kusiak; Elizaveta Kovaleva; Dennis Vanderliek; Harry Becker; Franziska Wilke; Anja Schreiber; Richard Wirth (Contributions to Mineralogy and Petrology, 2022)
Meteorite impact processes are ubiquitous on the surfaces of rocky and icy bodies in the Solar System, including the Moon. One of the most common accessory minerals, zircon, when shocked, produces specific micro-structures that may become indicative of the age and shock conditions of these impact processes. To better understand the shock mechanisms in zircon from Apollo 15 and 16 impact breccias, we applied transmission electron microscopy (TEM) and studied nano-structures in eight lunar zircons displaying four different morphologies from breccias 15455, 67915, and 67955. Our observations revealed a range of shock-related features in zircon: (1) planar and non-planar fractures, (2) “columnar” zircon rims around baddeleyite cores, (3) granular textured zircon, in most cases with sub-µm-size inclusions of monoclinic ZrO 2 (baddeleyite) and cubic ZrO 2 (zirconia), (4) silica-rich glass and metal inclusions of FeS and FeNi present at triple junctions in granular zircon and in baddeleyite, (5) inclusions of rutile in shocked baddeleyite, (6) amorphous domains, (7) recrystallized domains. In many grain aggregates, shock-related micro-structures overprint each other, indicating either different stages of a single impact process or multiple impact events. During shock, some zircons were transformed to diaplectic glass (6), and others (7) were completely decomposed into SiO 2 and Zr-oxide, evident from the observed round shapes of cubic zirconia and silica-rich glass filling triple junctions of zircon granules. Despite the highly variable effect on textures and Zr phases, shock-related features show no correlation with relatively homogeneous U–Pb or 207 Pb/ 206 Pb ages of zircons. Either the shock events occurred very soon after the solidification or recrystallization of the different Zr phases, or the shock events were too brief to result in noticeable Pb loss during shock metamorphism.